Euthanasia in detention and the ethics of caring solidarity: A case study of the ‘Tarragona Gunman’ - Espericueta, Luis (Bioethics, 2024)
Almost a year after the enactment of the law regulating euthanasia in Spain, public opinion was shocked to learn that a defendant in criminal proceedings obtained medical assistance in dying following injuries sustained in an exchange of gunfire with the police after having committed a series of severe crimes. Although there are very few cases in the world where prisoners have received euthanasia, the one we will discuss in this article is the only known case where both the public prosecutor's office and the private prosecutors judicially opposed the defendant's euthanasia. This article aims to offer a new perspective on the ethical legitimacy of detainees' access to euthanasia: the ethics of caring solidarity. To do this, we will first place the case in its legal context. Subsequently, we will address the two main arguments proposed in the literature to justify euthanasia in detention: respect for the autonomy of the detainee and the principle of equivalence of care. Finally, after having identified serious shortcomings in both arguments, we will argue that the perspective of caring solidarity offers a better ethical basis for people in detention's access to euthanasia.